Identification of a novel NKX2-5 variant in a young Ecuadorian patient with atrioventricular block and bradycardia: a case report - Ruiz-Pozo, Viviana A.; Cadena-Ullauri, Santiago; Paz-Cruz, Elius; Tamayo-Trujillo, Rafael; Guevara-Ramirez, Patricia; Onofre-Ruiz, Paul; Zambrano, Ana Karina (Frontiers in Cardiovascular Medicine, 2025)
Cardiovascular diseases (CVDs) are the leading global cause of mortality, with South America reflecting similar trends. Among congenital heart diseases (CHDs), atrioventricular (AV) block is included. AV block is a condition defined by abnormal electrical signal transmission between the atria and ventricles. Advances in Next-Generation Sequencing (NGS) have facilitated the identification of genetic variants associated with cardiac disorders, such as AV block. Notably, the transcription factor NKX2-5 plays a crucial role in heart development and function, and mutations in this gene have been linked to bradycardia and AV block. This article describes the case report of a young Ecuadorian child diagnosed with AV block and bradycardia. Furthermore, by performing NGS, a missense variant, p.(Tyr274Ser) substitution, in the NKX2-5 gene has been identified and classified as a variant of uncertain significance (VUS). Ancestral analysis has shown a genetic background of 16.5% African, 45.9% European, and 37.6% Native American. These findings suggest a potential association between the identified NKX2-5 variant and the patient's phenotype, highlighting the importance of integrating genomic and ancestral analyses to advance personalized diagnostics and therapeutics in diverse populations, such as the mestizo population.